Promising Markers of Preeclampsia : Cardiac Troponin 1 and Brain Natriuretic Peptide in Third Trimester Pregnant Women - Edebiri O.E.; Nwankwo A. A.; Akpe P. E.; Mbanaso E.L.; Ikuenobe V. E.; Omende K.; Ohiwerei W.O (International Forum of Researchers and Lecturers, 2025)
Cardiac Troponin1 (cTn1) is a protein released into the bloodstream following cardiac damage and Brain Natriuretic Peptide (BNP) is a hormone released by the heart in response to ventricular stretch and pressure overload. This study aims to investigate the predictive role of cTn1 and BNP in preeclamptic pregnant women in the third trimester of pregnancy. Forty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. Blood samples was spun in a bucket centrifuge at 2500 RPM (rounds per minute) for 10 minutes after which plasma was collected and stored frozen in plain sample bottles and was analyzed for Cardiac Troponin 1(cTn1) and Brain Natriuretic Peptide (BNP) by fluorescence immunoassay. Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. The present study showed that there was statistically significant increase in Brain Natriuretic Peptide (BNP) in preeclamptic women compared to normotensive pregnant women, indicating various underlying pathophysiological processes. These findings suggest the potential predictive roles of this cardiac marker in identifying and monitoring preeclampsia.